Interaction of Knowledge and HIV Test Intention Regarding HIV Tests and Breastfeeding Decisions - Rita Kirana; Nina Mardiana; Tut Barkinah; Vonny Khresna Dewi; Januarsih (Postgraduate, University of Mataram, 2023)
HIV transmission from mother to child tends to increase from year to year. One of the important ways of transmitting HIV is transmission from mother to fetus, however many pregnant women do not have the opportunity and information about HIV/AIDS and counseling services. This type of research is survey research. The population in this study was all pregnant women in the city of Balikpapan for the period 2021 - 2022 totaling 1.42 people. The sample in this study was pregnant women and met the inclusion and exclusion criteria. The results of the statistical test concluded that there was an interaction that had a significant and positive influence on HIV testing and the decision to provide breast milk in the city of Balikpapan, the knowledge factor influenced the seriousness that pregnant women felt about HIV/AIDS in carrying out HIV testing. Pregnant women who have high knowledge about HIV/AIDS will feel a very strong sense of seriousness about HIV/AIDS so with the seriousness they feel, the pregnant mother will be encouraged to carry out an HIV test. There are still many pregnant women who have low knowledge and do not undergo HIV testing because the education level of the respondents is still low, most of whom have a high school education or less.